Elimination by Gamification the 5th Grade Students’_x000D_ Misconceptions about the Matter and Phase Change - DURU, MEHMET KÜRŞAD; YILDIRIM, MEHTAP (My University, 2020)
While the purpose of this study is to reveal misconceptions about the Phase Change of Matter in thefifth grade Matter and Its Nature unit at the same time to overcome these misconceptions with gamified education.In accordance with these purposes, the "The Form of Misconceptions about Matter and Phase Change" consistingof four open-ended questions that was developed and implemented. This form was applied as a pre-and post-testto 20 students who are fifth grade students in the 2019-2020 academic year. While the instruction was carried outwithin the current teaching plan, the gamification components were added to the course and the intruction wasperformed. At the end of the study, it was determined that the students had difficulty in distinguishing the conceptsof evaporation and boiling, and they used the concept of smoke instead of vapor. After the course, which wascarried out using gamification components, it was determined that the students did not confuse the phase changesand could differentiate between the concepts of steam and smoke.